2020
DOI: 10.1108/md-08-2019-1078
|View full text |Cite
|
Sign up to set email alerts
|

External knowledge search and firms’ incremental innovation capability: the joint moderating effect of technological proximity and network embeddedness

Abstract: PurposeThis paper aims to analyze the extent to which the influence of external knowledge search activities on firms’ incremental innovation capability, and the moderating roles of the relatedness between the partners’ technological bases and a firm’s network embeddedness in the innovation network.Design/methodology/approachIn this empirical research, the authors collected a sample of patents in the UAV industry over the period of 2004–2018. Then the authors examined the direct role of external knowledge searc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
55
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(56 citation statements)
references
References 133 publications
0
55
0
1
Order By: Relevance
“…Second, although the impacts of knowledge search on innovation have been evaluated in prior studies from multiple perspectives such as organizational characteristics (Li et al, 2019), innovative network (Shi et al, 2020) and external environment (Ehls et al, 2020), the significance of organizational strategy in the knowledge search-innovation relationship (Li et al, 2010;Li et al, 2017) has been neglected in those studies. New evidence has shown that when organizations obtain the strategic capability to deal with innovation uncertainties, they can more effectively facilitate organizational knowledge search activities through flexible strategy adjustments (Rialti et al, 2020;Gilbert, 2005;Li et al, 2017).…”
Section: Theoretical Implicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, although the impacts of knowledge search on innovation have been evaluated in prior studies from multiple perspectives such as organizational characteristics (Li et al, 2019), innovative network (Shi et al, 2020) and external environment (Ehls et al, 2020), the significance of organizational strategy in the knowledge search-innovation relationship (Li et al, 2010;Li et al, 2017) has been neglected in those studies. New evidence has shown that when organizations obtain the strategic capability to deal with innovation uncertainties, they can more effectively facilitate organizational knowledge search activities through flexible strategy adjustments (Rialti et al, 2020;Gilbert, 2005;Li et al, 2017).…”
Section: Theoretical Implicationsmentioning
confidence: 99%
“…A thorough understanding of the linkage of ambidextrous leadership and organizational innovation has been achieved in this study, which echoes with Berraies and Abidine's (2019) call for the incorporation of knowledge factors into the relationship between ambidextrous leadership and innovation. Second, although the influence of knowledge search on innovation was evaluated in prior studies from multiple perspectives such as organizational characteristics (Li et al, 2019), innovative network (Shi et al, 2020) and external environment (Ehls et al, 2020), they neglected the significance of organizational strategy in the knowledge search-innovation relationship (Li et al, 2010;Li et al, 2017). As an organizational ability to flexibly adjust the allocation of resources to cope with changing innovation at the strategic level (Rialti et al, 2020), strategic flexibility offers excellent potential for the improvement in impacts of knowledge search on innovation by flexibly switching knowledge resources in innovative activities.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, a differentiation strategy is related to the organization’s innovative capacities and the ability to deliver new products and services that are not available through competitors (Cavusgil and Knight, 2015; Correia et al , 2020). Organizations with entrepreneurial orientations and growth through learning can support a differentiation strategy (Gatignon et al , 2002; Knight et al , 2020; Shi et al , 2020).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Nevertheless, organizations paying close attention to cumulative improvements in products and services must increase their organizational capacity and improve their resources to cope with developments in technology provided by other organizations and firms operating in the same industry (Shi et al , 2020; Rupietta and Backes-Gellner, 2019). Organizations must recognize that radical innovations delivered by competitors may destroy improved products and services through incremental innovation (González-Sánchez et al , 2020).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…We then explore the interaction of structural hole and centrality on competitive aggressiveness and network performance under different ego-network stability. Building on the resource-based view and social network theory, we argue that resources themselves are not competitive advantage, and a firm's ability of acquiring resources from network participants and transforming them into valuable resources is a firm's competitive advantage (Gulati and Gargiulo, 1999; Eisingerich et al , 2010; Shi et al , 2020). The structural hole and centrality are unique network position advantages to enable a firm to enjoy resource advantages.…”
Section: Introductionmentioning
confidence: 99%